Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1179/000349802125001212
|View full text |Cite
|
Sign up to set email alerts
|

Causative agents of liver abscess in those with liver cirrhosis: a 10-year case review of hospitalized patients in Thailand

Abstract: Although patients with cirrhosis of the liver show relative immunosuppression and therefore have increased susceptibility to most infections, they rarely develop liver abscesses. In a retrospective case review, the pathogens causing the liver abscesses observed, between January 1992 and December 2001 at the King Chulalongkorn Memorial Hospital, Bangkok, Thailand, in 44 hospitalized patients diagnosed as cases of liver cirrhosis were investigated. The most common clinical symptoms and signs of the abscesses--ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[1][2][3][4] Its emergence in western countries has also been reported. [5][6][7] Previous studies in Taiwan, Singapore and Korea found a high prevalence of the capsular polysaccharide (CPS) K antigen serotypes K1 (54.5-63.4%) and K2 (5-21.2%) of K. pneumoniae in liver abscess isolates.…”
mentioning
confidence: 99%
“…[1][2][3][4] Its emergence in western countries has also been reported. [5][6][7] Previous studies in Taiwan, Singapore and Korea found a high prevalence of the capsular polysaccharide (CPS) K antigen serotypes K1 (54.5-63.4%) and K2 (5-21.2%) of K. pneumoniae in liver abscess isolates.…”
mentioning
confidence: 99%
“…Amoebiasis of the genitourinary system is a rare parasitic disease [ 17 ]. The rupture of an infected liver abscess around the kidney, through the blood circulation or from the lymphatic system of the kidney and urinary system are the two main routes of transmission of genitourinary amoebiasis [ 18 , 19 ]. Free-living amoeba causes two rare central nervous system infections: primary amoebic meningoencephalitis and granulomatous amoebic encephalitis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…They often can be attributed to bacterial infections of the biliary tree such as cholangitis,9 or more distally in the body such as diverticulitis or inflammatory bowel disease,10 where infection may migrate to the liver via the portal vein system. Bacterial endocarditis, dental infections, fungal infections, cirrhosis,11 blunt trauma12 and foreign bodies13 are other causes. No cause is found in up to 15% of cases.…”
Section: Discussionmentioning
confidence: 99%